2008
DOI: 10.1080/10641960802068436
|View full text |Cite
|
Sign up to set email alerts
|

Increased Blood Pressure Levels Relative to Subjective Feelings of Intensity of Exercise Determined with the Borg Scale in Male Patients with Hypertension

Abstract: We examined the hemodynamic responses to exercise and symptoms in 37 male patients with untreated essential hypertension, and compared the findings with those in 32 age-matched healthy male volunteers by performing a graded symptom-limited exercise test using a bicycle ergometer. The subjective feeling of intensity of exercise was determined using the Borg scale. In the relationship between Borg scores and blood pressure (BP), patients with hypertension showed higher systolic BP and diastolic BP relative to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Additional studies were excluded on study report characteristics ( k = 190), study type ( k = 13), outcome measures ( k = 53), or comparison ( k = 9). The remaining 43 studies (Piepoli et al, 1996 ; Cacioppo et al, 2000 ; Perini et al, 2000 ; Steptoe et al, 2002 , 2005 ; Wood et al, 2002 ; Bartels Matthew et al, 2003 ; Kunz-Ebrecht et al, 2003 ; Takahashi et al, 2003 ; Steptoe and Marmot, 2005 , 2006 ; Davrath Linda et al, 2006 ; Hamer and Steptoe, 2007 ; Virtanen et al, 2007 ; Mayumi et al, 2008 ; Karavirta et al, 2009 ; Petrofsky et al, 2009 ; Dourado et al, 2010 ; Alves Naiane Ferraz et al, 2011 ; Millar et al, 2011 ; Sales et al, 2011 ; Wang Norman et al, 2011 ; Capuana et al, 2012 ; Archiza et al, 2013 ; CorrĂȘa et al, 2013 ; Christensen Stephanie and Wright Heather, 2014 ; Collste et al, 2014 ; Lin et al, 2014 , 2017a ; Machado-Vidotti et al, 2014 ; Ahmadian and Dabidi Roshan, 2015 ; Crowley Olga et al, 2016 ; Norcliffe-Kaufmann et al, 2016 ; Wawrzyniak Andrew et al, 2016 ; Beer et al, 2017 ; Beer Noa et al, 2017 ; Betz Linda et al, 2017 ; Junior Adalberto et al, 2019 ; Kuraoka et al, 2019 ; Perpetuini et al, 2019 ; Rodrigues Jhennyfer et al, 2019 ; Wittstein et al, 2019 ; Kaltsatou et al, 2020 ) were included for the qualitative synthesis and—in case of sufficient quality and data reporting—considered for the meta-analyses ( k = 18). Consider Figure 1 for a detailed overview of the study selection.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additional studies were excluded on study report characteristics ( k = 190), study type ( k = 13), outcome measures ( k = 53), or comparison ( k = 9). The remaining 43 studies (Piepoli et al, 1996 ; Cacioppo et al, 2000 ; Perini et al, 2000 ; Steptoe et al, 2002 , 2005 ; Wood et al, 2002 ; Bartels Matthew et al, 2003 ; Kunz-Ebrecht et al, 2003 ; Takahashi et al, 2003 ; Steptoe and Marmot, 2005 , 2006 ; Davrath Linda et al, 2006 ; Hamer and Steptoe, 2007 ; Virtanen et al, 2007 ; Mayumi et al, 2008 ; Karavirta et al, 2009 ; Petrofsky et al, 2009 ; Dourado et al, 2010 ; Alves Naiane Ferraz et al, 2011 ; Millar et al, 2011 ; Sales et al, 2011 ; Wang Norman et al, 2011 ; Capuana et al, 2012 ; Archiza et al, 2013 ; CorrĂȘa et al, 2013 ; Christensen Stephanie and Wright Heather, 2014 ; Collste et al, 2014 ; Lin et al, 2014 , 2017a ; Machado-Vidotti et al, 2014 ; Ahmadian and Dabidi Roshan, 2015 ; Crowley Olga et al, 2016 ; Norcliffe-Kaufmann et al, 2016 ; Wawrzyniak Andrew et al, 2016 ; Beer et al, 2017 ; Beer Noa et al, 2017 ; Betz Linda et al, 2017 ; Junior Adalberto et al, 2019 ; Kuraoka et al, 2019 ; Perpetuini et al, 2019 ; Rodrigues Jhennyfer et al, 2019 ; Wittstein et al, 2019 ; Kaltsatou et al, 2020 ) were included for the qualitative synthesis and—in case of sufficient quality and data reporting—considered for the meta-analyses ( k = 18). Consider Figure 1 for a detailed overview of the study selection.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, two studies showed no between-group differences in vagally-mediated HRV [i.e., HFnu (Wood et al, (Kaltsatou et al, 2020). Higher intensities of exercise and higher heart rate were related to larger reductions of mRR (Virtanen et al, 2007), HF (Mayumi et al, 2008;Archiza et al, 2013), LFnu (Perini et al, 2000), LF/HF (Perini et al, 2000), and DFA-α1 (Karavirta et al, 2009) as well as larger increases in HFnu (Perini et al, 2000) during exercise. The addition of gait synchronization elevated DFA-α during walking (Wittstein et al, 2019).…”
Section: Phasic Hrv Responses To Cognitive Exercisesmentioning
confidence: 92%
See 3 more Smart Citations